The Analysis of Determinant Factors of Poverty And Its Effect Toward Economic Development of Islamic Society : Case Study at Serdang Bedagai Regency At North Sumatera Province - Muhammad Zilal Hamzah; Zainuddin Siregar (Indonesian Management and Accounting Research, 2012)
in the last two decades. Indonesia has experienced contrasting episodes in terms of economic growth and changes in the pm erty rate. Prior middle 1980s until middle 19903. Indonesia experienced a high economic growth and a rapid reduction in poverty. During the economic crisis period of 1997-1999, however. the economy contracted substantially and poverty increased signit‘lcantly. wiping out many years of progress. Post-crisis. economic growth slowly recovered. but the poverty rate declined much faster falling to below the pre-crisis level. These contrasting episodes of growth and poverty trends provide the opportunity to empirically assess the relationship between economic development and poverty. Study of this relationships. usually divide the economy into three sectors: agriculture. industry. and services. The mechanism ofthe relationships between economic development and change in poverty must be better understood in order to formulate the most effective strategy for poverty reduction through macroeconomic policy. Therefore. this research tries to examine more specific than previous studies. that is the effect ofdetemiinant factors (such as: level of fonnal education. level ofsocial economic. agriculture land ownership. lslamicjob tradition) ofpm erty toward economic development. This research is done at Serdang Bedagai Regency at North Suimatera Province. The research hypothesis states that [m el of formal education and agriculture land ownership effect economic development significantly. Otherwise. level of social economic and Islamic job tradition insignificantly effect economic developmentKeywords: level of formal education. level of social economic. agriculture land ownership. Islamic job tradition, poverty. economiy development.